Trajectories of Random Quadratic Operators of the Random Mendelian Model of Heredity - Ganikhodjaev, Nasir; Moin, Noor Hasnah; Mior Othman, Wan Ainun; Hamzah, Nor Aishah (Universiti Putra Malaysia Press, 2004)
It is considered random Mendelian model of heredity, when the random quadratic stochastic operators, which define this model, admit two values and Vii' where 0 :s; a :s; I, 0 :s; f3:S; 1. This paper provides a full description of the behaviour of random trajectories of random quadratic operators.